El Excentrico, 1973-08-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
August 5, 1973 [5 de agosto de 1973]. No volume or issue number. Cover has a photograph of the 1973 Union City Queen, Rosa Maria Vela, and her court from the American G.I. Forum.